Demand for Patent Literature and Supply Service in India - Joseph, A.; Rajan, T. N. (Journal of Information and Knowledge, 1981)
Focusses Insdoc's experience In handling patent demands, procurement and supply service. An analysis of data on the service for the last five years (1972-75) is presented. A brief survey of world patent sources and services is made. Indicates the possible future trends in the patent system and consequently the patent information system.